Operation Rule Study of Electronic Expansion Valve in ASHPWH with Economizer - Li Yuchun; Cai Zhihong; He Yongfeng (Zhileng xuebao)
A heat pump with economizer is studied by experiment under the conditions: dry-bulb temperature of inlet air is from -15℃ to +20℃, while inlet water is from 33℃ to 55℃.By change the opening of the electronic expansion valves in the main pipe line as well as in the injection pipe line, it shows that the main pipe line valve optimum opening is getting smaller when inlet water is getting warmer,and optimum opening is getting larger when inlet air is getting warmer,while the injection pipe line valve optimum opening goes oppositely . Some analysis and explanation on the rule is carried out. The rule can be used to guide to product optimization.